A Review of Present Advancement in Climate Smart Agriculture Techniques: Adaptation for Sustaining Crop Production under Climate Change - , Niru Kumari; , Amit Kumar Pandey; , Akhilesh Kumar Singh; , Ashutosh Singh (Archives of Current Research International, 2024)
The growing global population is driving up demand for agricultural goods at a never-before-seen rate. Improving crop yield and quality is essential to meeting this growing demand. The yield and quality of agricultural crops may be greatly increased by using agronomic techniques. Although it is known that changing climate circumstances have a detrimental impact on crop development, yield, soil quality, and ultimately the nutritional content of agricultural food, such agronomic methods under changing climate conditions are insufficient to boost crop productivity. In order to increase the production potential of agricultural crops, several agronomic improvements have been made in the previous few decades. These include the application of resource conservation technology and conservation agricultural methods. Therefore, it is essential to adopt various adaptive agricultural practices that are specifically resource-conserving, such as crop diversification, mulching, crop rotation, agroforestry, intercropping, and the push-pull system of crop pest and disease management, etc. in order to effectively deal with such unfavourable situations. These agronomic approaches, which are being advocated to increase agricultural production and profitability, are described in the review along with their methods for enhancing crop performance and quality.